2021
DOI: 10.1007/s00705-020-04947-2
|View full text |Cite
|
Sign up to set email alerts
|

Replicative capacity of four porcine enteric coronaviruses in LLC-PK1 cells

Abstract: Enteric coronaviruses (CoVs) are major pathogens that cause diarrhea in piglets. To date, four porcine enteric CoVs have been identified: transmissible gastroenteritis virus (TGEV), porcine epidemic diarrhea virus (PEDV), porcine deltacoronavirus (PDCoV), and HKU2-like porcine enteric alphacoronavirus (PEAV). In this study, we investigated the replicative capacity of these four enteric CoVs in LLC-PK1 cells, a porcine kidney cell line. The results showed that LLC-PK1 cells are susceptible to all four enteric C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 25 publications
(31 reference statements)
0
4
0
Order By: Relevance
“…Currently, PEDV has been reported to mainly infect porcine cells such as IEC(11), IPEC-J2 ( 35 , 36 ), and LLC-PK1 ( 37 ). However, we found that the infection of PEDV to LLC-PK1 cells was strain-specific.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, PEDV has been reported to mainly infect porcine cells such as IEC(11), IPEC-J2 ( 35 , 36 ), and LLC-PK1 ( 37 ). However, we found that the infection of PEDV to LLC-PK1 cells was strain-specific.…”
Section: Discussionmentioning
confidence: 99%
“…It is similar by structure but very distinct in the type of target cell from the porcine respiratory coronavirus (PRCV), which aff ects the respiratory system. Th e latter has been shown to arise from TGEV by deletion of part of the viral protein S, resulting in a change in the tropism of the virus from the gastrointestinal tract to the respiratory tract [41].…”
Section: Fractionation and Affi Nity Chromatography Th Is Work Used T...mentioning
confidence: 99%
“…The swine enteric coronaviruses offer a more suitable model for investigating coronaviral coinfections and recombination than coronaviruses that cause respiratory diseases. Different swine enteric coronaviruses can infect the same cells, providing the temporal and spatial conditions for genetic recombination [ 27 ]. These viruses also show tropism for the jejunum and ileum of piglets, providing favorable conditions for recombination during natural infections [ 4 , 28 ].…”
Section: Introductionmentioning
confidence: 99%